The effectiveness of teaching chest compression first in a standardized public cardiopulmonary resuscitation training program. Issue 13 (March 2019) - Hsu, Shou-Chien; Kuo, Chan-Wei; Weng, Yi-Ming; Lin, Chi-Chun; Chen, Jih-Chang
Abstract : Abstract: Effectiveness of bystander cardiopulmonary resuscitation (CPR) is known to provide emergency medical services which reduce the number of deaths in patients with out-of-hospital cardiac arrest. The survival at these patients is affected by the training level of the bystander, but the best format of CPR training is unclear. In this pilot study, we aimed to examine whether the sequence of CPR instruction improves learning retention on the course materials. A total of 95 participants were recruited and divided into 2 groups; Group 1: 49 participants were taught firstly how to recognize a cardiac arrest and activate the emergency response system, and Group 2: 46 participants were taught chest compression first. The performance of participants was observed and evaluated, the results from 1 pre-test and 2 post-tests between 2 groups were then compared. There was a significantly better improvement of participants in Group 2 regarding the recognition of a cardiac arrest and the activation of the emergency response system than of those in Group 1. At the post-test, participants in Group 2 had an improvement in chest compression compared to those in Group 1, but the difference was not statistically significant. Our study had revealed that teaching CPR first in a standardized public education program had improved the ability of participants to recognize cardiac arrest and to activate the emergency response system. Abstract : Supplemental Digital Content is available in the text